Patterns of spectral, spatial, and long‐term variability in light attenuation in an optically complex sub‐estuary. (23rd July 2018) - Rose, Kevin C.; Neale, Patrick J.; Tzortziou, Maria; Gallegos, Charles L.; Jordan, Thomas E.
Abstract : The attenuation of solar radiation controls many processes and characteristics of aquatic ecosystems and is a sentinel of larger‐scale environmental change. While light attenuation is often characterized with a single broadband diffuse attenuation coefficient of photosynthetically active radiation ( K d PAR), attenuation can exhibit substantial variability across the solar spectrum and through time and space. Understanding this variability and its proximate causes may provide information to characterize large‐scale environmental change. We implemented a semi‐analytical K d model in four segments of the Rhode River sub‐estuary of the Chesapeake Bay to examine spectral, spatial, and temporal variability in K d across the ultraviolet (UV) to PAR wavelengths (290–710 nm) over the period 1986–2014. We used this model to identify wavelengths most sensitive to long‐term change, the seasonal phenology of long‐term change, and the optical constituents driving changes. The model included contributions by phytoplankton, non‐algal particulates, chromophoric dissolved organic matter (CDOM), and water. Over the period of record, K d increased (water transparency decreased) in both UV and PAR wavelengths, with the largest increases at the most upstream site, during summer months, and at short UV wavelengths. These increases were due primarily to an increase in non‐algal particulates, and particularly since year 2005, however there was substantial seasonality in K d . The model reveals how different changes in water quality have a differential effect on UV and PAR attenuation, and enables insight into what types of long‐term change in transparency have occurred over the long period of human impacts in the Chesapeake Bay watershed.